"That song moves me to tears" – Emotion, memory and identity in encountering Christian songs - Tönsing, J. Gertrud (HTS teologiese studies, 2020)
This article aims to explore the complex issue of the emotive effect of Christian songs. It is based mainly on a literature survey, using sources both from Christian hymnology and musicology. It also uses illustrative examples from three informal surveys in congregations on the reasons particular songs are favourites. The point is made that exploring this issue scientifically is very complex as there are so many variables in people’s appreciation of songs. Some of these elements are discussed, such as the effect of the external setting in which people experience a song, factors important in the appreciation of a text, such as poetic quality and knowledge of the author’s background. Other factors are the emotive quality and level of difficulty of a tune and in what time this style was popular. Then there are the internal factors, such as the link of a song with group identity and special memories. Some of the survey results corroborate the pointers in the literature for what makes certain songs particularly emotionally appealing. Some of these were a preference for musical styles popular in one’s youth, the importance of relationships with significant others for forming favourites and the important element of memory in the emotional impact of songs. Concluding pointers for worship include motivating for different styles of music in worship and carefully finding those songs in each new musical genre, which have the potential for sustaining today’s youth into the future.Contribution: This article makes a contribution in what is a complex and often emotionally charged issue in congregations: Worship styles and musical preferences. It argues for the importance of using different musical styles and bringing the generations together.